OPTIMALISASI KOMPETENSI RADIOGRAFER MELALUI PELATIHAN PELAYANAN PRIMA UNTUK MEWUJUDKAN LAYANAN RADIOLOGI YANG PROFESIONAL, RAMAH, DAN BERORIENTASI PASIEN - Angella, Shelly; Bisra, Marido; Zaky, Abdul (Awal Bros Journal of Community Development, 2025)
Excellent service in radiography is essential for enhancing patient satisfaction and improving the efficiency of healthcare services. Excellent service in healthcare is one of the key factors in improving the quality of patient care. Radiographers, as healthcare professionals responsible for radiological examinations, play a significant role in providing optimal services. However, various challenges persist in radiology services, such as ineffective communication, lack of empathy, and limited understanding of patient needs. Therefore, training in excellent service for prospective radiographers has become an urgent necessity. This program aims to provide training on excellent service for prospective radiographers. The training covers effective communication, professional ethics, and quality service techniques. It also seeks to enhance the competencies of prospective radiographers in delivering excellent service in terms of communication, technical skills, and professionalism. The training methods include theoretical sessions, case studies, and hands-on simulations with patients. The results indicate a significant improvement in the service skills of the training participants. Additionally, the training results show an increase in participants' understanding and ability to provide friendlier, more efficient, and patient-centered services. Feedback from the participants suggests that interactive and practice-based learning methods are highly beneficial in understanding the concept of excellent service. In conclusion, this training contributes to better preparing prospective radiographers for workplace challenges and improving the quality of radiology services in healthcare facilities